2020
DOI: 10.1017/s000711452000210x
|View full text |Cite
|
Sign up to set email alerts
|

Effects ofin ovofeeding of vitamin C on post-hatch performance, immune status and DNA methylation-related gene expression in broiler chickens

Abstract: This study aimed to evaluate the effect of in ovo feeding (IOF) of vitamin C at embryonic age 11 (E11) on post-hatch performance, immune status and DNA methylation-related gene expression in broiler chickens. A total of 240 Arbor Acres breeder eggs (63 (sem 0·5) g) were randomly divided into two groups: normal saline and vitamin C (VC) groups. After incubation, newly hatched chicks from each group were randomly divided into six replicates with ten chicks per replicate. Hatchability, average daily feed intake (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 36 publications
0
22
0
3
Order By: Relevance
“…Current studies suggested that the pro-apoptotic/anti-oxidative effects of vitamin C are related to the pro-oxidative/anti-oxidative effects in cells, which can Accepted manuscript induce apoptosis at high doses of vitamin C (35)(36)(37) . Nevertheless, the prior study showed that IOF of 3 mg vitamin C at E11 could increase the total antioxidant capacity of plasma at D 42, and had no significant effect on the levels of glutathione peroxidase, superoxide dismutase and malonaldehyde (6) . Zhang et al (15) reported that IOF of 12 mg ascorbic acid at E 17 could reduce the level of malonaldehyde in plasma and thus had a positive effect on the antioxidant capacity of broilers.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Current studies suggested that the pro-apoptotic/anti-oxidative effects of vitamin C are related to the pro-oxidative/anti-oxidative effects in cells, which can Accepted manuscript induce apoptosis at high doses of vitamin C (35)(36)(37) . Nevertheless, the prior study showed that IOF of 3 mg vitamin C at E11 could increase the total antioxidant capacity of plasma at D 42, and had no significant effect on the levels of glutathione peroxidase, superoxide dismutase and malonaldehyde (6) . Zhang et al (15) reported that IOF of 12 mg ascorbic acid at E 17 could reduce the level of malonaldehyde in plasma and thus had a positive effect on the antioxidant capacity of broilers.…”
Section: Discussionmentioning
confidence: 91%
“…The eggs were injected on embryonic day (E) 11 (6) . The experimental treatment is as follows: 1) the CON group was injected with normal saline, and the injection volume was 0.1 mL; 2) the VC group was injected with the same volume of vitamin C (Sigma-Aldrich Inc., USA) solution with concentration of 30 mg/mL (6) . The injection procedure is as follows: Removing the embryo-free eggs and dead sperm eggs, and determine the position of the yolk sac after candling; sterilize the air chamber with 75% alcohol, and drill a hole with the diameter of about 1 mm, then, sterilize the surrounding area with 75% alcohol again; the nutrients were slowly injected into the yolk sac of the embryo egg with 1 mL syringe.…”
Section: Embryo Egg Incubation Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…(63): при инъекции 11-суточным эмбрионам аскорбиновой кислоты (3 мг/яйцо) наблюдали и улучшение выводимости, и увеличение скорости роста цыплят до 42-суточного возраста. Более того, те же авторы обнаружили повышение экспрессии генов IL-4 и DNMT1 и снижение -IL-1, Tet 2, Tet 3 и Gadd 45 (р < 0,05) в тканях селезенки у 21-суточных цыплят, получавших аскорбиновую кислоту на 11-е сут инкубации (63). По-видимому, эффект антиоксидантов зависит от особенностей жирнокислотного состава яйца и содержания эндогенных антиокислителей.…”
unclassified